Teaching El eterno femenino by Rosario Castellanos: “The Dreams of Reason produce Monsters” (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
In The Eternal Feminine, a farce, written by Rosario Castellanos (Mexico, 1925-1974), the effect of sexism on women is dramatized in a comic, exaggerated form to raise the consciousness of women about the pernicious consequences of feminine passivity, inauthenticity, and self-sacrifice. The article characterizes the play’s text using Castellanos’ essays to explain some of its more elusive meanings. It discusses the experience of teaching the play in advanced university classes in the U.S.A. with teaching goals as diverse as to improve the Spanish of the students, to inform them about the history of ideas in Mexico, and to teach methods of cultural and literary critical analysis.